Konsep Waktu Dalam Teologi Agustinus Menurut Telaah Atas Confessions dan City of God - Bildath Imanuel Bili; Tjiauw Thuan Alias Hali (STT Saint Paul Bandung, 2025)
This paper specifically explores Augustine’s thought on the concept of time. Drawing on his two major works, Confessions and City of God, the discussion focuses on four main aspects: Augustine’s understanding of time, the theological origin of time, the relationship between God and time, and the human condition as beings who live within time. The discussion will conclude with the author’s analysis and reflection based on Augustine’s formulation of the concept of time. The method employed is the qualitative method, which done by historical methodology. This research is done by exploring two Augustine’s works that explicitly address the notion of time. The results of the study show the relationship between time and God and the relationship between time and humans. God transcends and overcomes time where time only began to exist after God created it as He also created other creatures. Humans live in time and space, so humans should live their days with full responsibility as if they only lived today or now.